2022
DOI: 10.1590/1519-6984.263047
|View full text |Cite
|
Sign up to set email alerts
|

Histological biomarkers and biometric data on trahira Hoplias malabaricus (Pisces, Characiformes, Erythrinidae): a bioindicator species in the Mearim river, Brazilian Amazon

Abstract: The objective of this study was to evaluate the levels of environmental contamination in a protected area in the Brazilian Amazon. For this, two areas were chosen along the Mearim River: the reference area (A1) and the potentially contaminated area (A2), where water samples were collected, for physicochemical and microbiological analyses, as well as specimens of Hoplias malabaricus, for the evaluation of biometric data and incidence of branchial lesions. The physicochemical analyzes of the water from both area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
0
0
0
Order By: Relevance
“…Similar lesions were also registered by other studies for this same species in two areas in the region of the Complexo Estuarino de São Marcos -MA (Castro et al, 2018;Viana et al, 2021) and in gills of Oreochromis niloticus (Linnaeus, 1758) from the Laguna da Jansen (area with a history of contamination by domestic effluents), São Luís, Brazil (Pereira et al, 2014). Freitas et al (2022) found other types of branchial lesions (hyperplasia, lamellar disorganization, proliferation of mucous cells and dilation of venous sinuses and congestion) in Hoplias malabaricus in two stretches of the Mearim River in the Baixada Maranhense region. Morphological changes in gills and impairment of their functions are considered indicative of cumulative chemical or physical changes in the immediate vicinity of the organism's habitat, given that they are structures with a large surface area and interact extensively with water (Jerome et al, 2017).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Similar lesions were also registered by other studies for this same species in two areas in the region of the Complexo Estuarino de São Marcos -MA (Castro et al, 2018;Viana et al, 2021) and in gills of Oreochromis niloticus (Linnaeus, 1758) from the Laguna da Jansen (area with a history of contamination by domestic effluents), São Luís, Brazil (Pereira et al, 2014). Freitas et al (2022) found other types of branchial lesions (hyperplasia, lamellar disorganization, proliferation of mucous cells and dilation of venous sinuses and congestion) in Hoplias malabaricus in two stretches of the Mearim River in the Baixada Maranhense region. Morphological changes in gills and impairment of their functions are considered indicative of cumulative chemical or physical changes in the immediate vicinity of the organism's habitat, given that they are structures with a large surface area and interact extensively with water (Jerome et al, 2017).…”
Section: Discussionmentioning
confidence: 86%
“…The presence of contaminants in the aquatic environment can influence the health of organisms present there, causing various damages to tissues (Noleto et al, 2022;Freitas et al, 2022). Next, we will highlight the morphological changes found in gill and liver tissues of S. herzbergii.…”
Section: Discussionmentioning
confidence: 98%